Study design and rationale for the TETON phase 3, randomised, controlled clinical trials of inhaled treprostinil in the treatment of idiopathic pulmonary fibrosis. Issue 1 (4th July 2022) - Nathan, Steven D; Behr, Jurgen; Cottin, Vincent; Lancaster, Lisa; Smith, Peter; Deng, CQ; Pearce, Natalie; Bell, Heidi; Peterson, Leigh; Flaherty, Kevin R
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) greatly impacts quality of life and eventually leads to premature death from respiratory failure. Inhaled treprostinil was associated with improvements in forced vital capacity (FVC) and reduced exacerbations of underlying lung disease in post hoc analyses from a phase 3 study in patients with precapillary pulmonary hypertension due to interstitial lung disease. These results, combined with preclinical evidence of treprostinil's antifibrotic activity, support its investigation in the treatment of IPF. Methods and analysis: The TETON programme consists of two replicate, 52-week, randomised, double-blind placebo-controlled, phase 3 studies, each enrolling 396 subjects (NCT04708782, NCT05255991 ). Eligible subjects must have a diagnosis of IPF confirmed by central imaging review, along with an FVC ≥45%. Stable background use of pirfenidone or nintedanib is allowed. The primary endpoint is change in absolute FVC at week 52. Secondary endpoints include time to clinical worsening (first event of death, respiratory hospitalisation or ≥10% decline in % predicted FVC), time to first acute exacerbation of IPF, overall survival, change in % predicted FVC and change in the King's Brief Interstitial Lung Disease Questionnaire at week 52. Safety parameters include adverse events, hospitalisations, oxygenation and laboratory parameters. Patients who complete week 52 will be eligible to enter an open-label extension study. Ethics and dissemination: Studies will be conducted in accordance with the International Conference on Harmonisation Guideline for Good Clinical Practice, Declaration of Helsinki principles, and local regulatory, ethical and legal requirements. Results will be published in a peer-reviewed publication.